Yersinia pestis, the cause of plague, is a recently emerged clone of Yersinia pseudotuberculosis - Achtman, Mark (National Academy of Sciences, 1999)
Plague, one of the most devastating diseases of human history, is caused by Yersinia pestis. In this study, we analyzed the population genetic structure of Y. pestis and the two other pathogenic Yersinia species, Y. pseudotuberculosis and Y. enterocolitica. Fragments of five housekeeping genes and a gene involved in the synthesis of lipopolysaccharide were sequenced from 36 strains representing the global diversity of Y. pestis and from 12–13 strains from each of the other species. No sequence diversity was found in any Y. pestis gene, and these alleles were identical or nearly identical to alleles from Y. pseudotuberculosis. Thus, Y. pestis is a clone that evolved from Y. pseudotuberculosis 1,500–20,000 years ago, shortly before the first known pandemics of human plague. Three biovars (Antiqua, Medievalis, and Orientalis) have been distinguished by microbiologists within the Y. pestis clone. These biovars form distinct branches of a phylogenetic tree based on restriction fragment length polymorphisms of the locations of the IS100 insertion element. These data are consistent with previous inferences that Antiqua caused a plague pandemic in the sixth century, Medievalis caused the Black Death and subsequent epidemics during the second pandemic wave, and Orientalis caused the current plague pandemic.